Irreversible Respiratory Failure in a Full-Term Infant with Features of Pulmonary Interstitial Glycogenosis as Well as Bronchopulmonary Dysplasia - Jiskoot-Ermers, Maresa E. C.; Antonius, Tim A. J.; Looijen-Salamon, Monika G.; Wijnen, Marc H. W. A.; Loza, Bettina F.; Heijst, Arno F. J. van (American Journal of Perinatology Reports, 2015)
Pulmonary interstitial glycogenosis (PIG) is a rare interstitial lung disease in the newborns. We report on the clinical presentation and pathological findings of a full-term male infant with pulmonary hypertension requiring extracorporeal membrane oxygenation (ECMO). An open lung biopsy demonstrated interstitial changes resembling pulmonary interstitial glycogenosis as well as bronchopulmonary dysplasia (BPD), without convincing evidence of maturational arrest, infection, alveolar proteinosis, or alveolar capillary dysplasia. The boy was treated with glucocorticoids and, after a few days, was weaned from ECMO. A few hours later, the patient died due to acute severe pulmonary hypertension with acute right ventricular failure. The etiology and underlying pathogenic mechanisms of PIG are unknown. The clinical outcomes are quite varied. Deaths have been reported when PIG exists with abnormal lung development and pulmonary vascular growth and congenital heart disease. No mortality has been reported in PIG together with BPD in full-term infants. In this article, we reported on a full-term infant with interstitial changes resembling PIG and BPD who expired despite no convincing evidence of an anatomical maturational arrest or congenital heart disease.
Keywords: pulmonary interstitial glycogenosis; respiratory failure; interstitial lung disease; ECMO; pulmonary hypertension